Day 2 Tue, August 28, 2018 2018
DOI: 10.2118/191105-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthesized AMPS-g-Clay/CuO NanoComposite on WBDFS for Challenging Formations

Abstract: An attempt has been made in this work to formulate a novel water based mud system with acrylamido-methyl-propane sulfonate polymer (AMPS) grafted clay/CuO nanocomposite for drilling the high temperature troublesome shale formations. Literature survey found several water mud applications of AMPS polymers in the high temperature and high salinity environment as they are highly water-soluble anionic additives. On the other hand, investigators have reported very encouraging results on rheology and fluid loss contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Platinum coating was used since it reduces the required coating thickness by half relative to the commonly used gold coating. The thinner coating better reveals the fine microstructure and is less affected by the temperature and substrate composition [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum coating was used since it reduces the required coating thickness by half relative to the commonly used gold coating. The thinner coating better reveals the fine microstructure and is less affected by the temperature and substrate composition [23].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the strong initial dispersion of the nanoclay in the HPAM solution, by virtue of hydrogen bonding, reduced the extent of polymer chain degradation [12] and maintained a higher extent of entanglement among the polymer chains at the higher shear rate. Moreover, the adsorption of CuO NPs onto the polymer strengthens the entanglement among the polymer chains, which reduces the shear sensitivity of the polymer [23]. It is noted that during polymer flooding, the polymer molecules are subjected to high levels of shearing, especially at the exit of the injector well [3,12].…”
Section: Rheological Behavior Of the Hpam Solution And The Nanohybridmentioning
confidence: 99%
“…In addition, the presence of bentonite enhances the mud cake formation tendency by virtue of its better adsorption and flocculation during the buildup of the filter cake (KoK 2010; Jain et al 2015). Low fluid loss is desired in order to restrict the physicochemical interaction inside the borehole which may lead to wellbore instability issues (Kumar et al 2018).…”
Section: Effect Of Bentonite On the Rheological And Filtration Propermentioning
confidence: 99%
“…Particle radius, nm Other variables: 500-mL mud system, 10 g bentonite, 2.5 g PAC-LVG, 1.5 g SLS and 0.5 g XG damage the formation (Jain et al 2015). Kumar et al (2018) reported that the majority of wellbore instability occurs due to fluid loss and rock fluid interaction. Thus, it is evident that engineered drilling fluids can be designed to suspend particles within certain range that are best suited for a given formation.…”
Section: Particle Size Distribution Of the Imme (O/w) Emulsion Mudmentioning
confidence: 99%
“…One of these industries is the oil and gas industry, where the revolution of nanotechnology applications covered different areas in both upstream and downstream. A quick look at the recent published applications related to nanotechnology reveals a wide range of nanoterminology such as nanoparticles (Sensoy et al 2009;Ogolo et al 2012;Hafiz et al 2018), nanocomposite (Lecolier et al 2005;Pourafshary et al 2009;Chauhan and Ojha 2016;Kumar et al 2018), nanomembrane (Seland et al 1992; Kong and Ohadi 2010;Shen and Sheng 2016;Guo et al 2013;Ventura et al 2017;Folio et al 2018), nanosensors (Sudarshan et al 2001;Piantanida et al 2013), nanorobot (Singh and Bhat 2006;Joshua 2014), nanofluids (Kanj et al 2009;Alomair et al 2014;Gerogiorgis et al 2017;Yuan and Moghanloo 2018).…”
Section: Introductionmentioning
confidence: 99%